Analysis of The Effect of Service Quality and Company Image on Customer Loyalty at Graha Elektronik Store in Palembang City Mediated by Customer Satisfaction - Michel Vincencia; Elia Ardyan (International Journal of Review Management Business and Entrepreneurship (RMBE), 2023)
This study aims to examine the influence of service quality and corporate image on customer loyalty through customer satisfaction as a mediating variable at Toko Graha Elektronik in Palembang City. The variables studied were service quality (X1), corporate image (X2), customer satisfaction (M) and customer loyalty (Y). The analysis tool used is SEM-PLS. The population in this study are customers of Toko Graha Elektronik who have made purchases at least twice with a sample of 180 respondents. The results showed that service quality has an effect on customer satisfaction, company image has an effect on customer satisfaction, service quality has no effect on customer loyalty, company image has no effect on customer loyalty, customer satisfaction has an effect on customer loyalty, service quality has an effect on customer loyalty through customer satisfaction as a mediating variable, and corporate image has no effect on customer loyalty through customer satisfaction as a mediating variable at Toko Graha Elektronik in Palembang City.